Manipulation of the optical properties in colloidal quantum wells: towards efficient laser applications - Zhang, Zitong (Nanyang Technological University, 2022)
Colloidal two-dimensional (2-D) nanoplatelets (NPLs), namely colloidal quantum wells, have received tremendous attention as promising gain media in the last few years owing to their excellent solution processability, broad wavelength tunability, huge absorption cross-sections, ultra-narrow linewidths, and strongly inhibited Auger effect. Despite the considerable progress achieved in NPLs-based microlasers, the realization of facile lasers with high-quality and low-threshold remains a grand challenge. Most importantly, the crucial optoelectrical properties of NPLs have not been explored to the same extent as the synthesis of novel 2-D nanostructures or the fabrication of corresponding prototype devices, which impedes a deep understanding of the physical insights into NPLs systems and, in turn, hampers the accurate prediction and rational design of NPLs-based optoelectronics. Thus, it is necessary to investigate the underlying rich photophysics in the NPLs family and to explore versatile approaches to construct functionalized NPLs-microlasers. To this end, this dissertation will cover the optimized synthesis of CdSe-based NPLs with broad spectral coverage, the investigation of the underlying mechanisms of light-matter interactions in quantum-well structures through various spectroscopy techniques, and the fabrication of miniaturized laser sources containing NPLs with the robust and high-quality operation.